2020
DOI: 10.1111/ijcp.13674
|View full text |Cite
|
Sign up to set email alerts
|

“Stay at Home, Protect the National Health Service, Save Lives”: A cost benefit analysis of the lockdown in the United Kingdom

Abstract: Introduction The COVID‐19 pandemic has transformed lives across the world. In the UK, a public health driven policy of population ‘lockdown’ has had enormous personal and economic impact. Methods We compare UK response and outcomes with European countries of similar income and healthcare resources. We calibrate estimates of the economic costs as different % loss in Gross Domestic Product (GDP) against possible benefits of avoiding life years lost, for different scenario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 32 publications
(58 reference statements)
1
104
0
Order By: Relevance
“…However, regional success stories involving, for instance, local test or tool production were reported from South Africa and Rwanda 95,96 . Although some initial cost estimates of the COVID19 disruption in the health care industry have been published [97][98][99] , they are likely to be too preliminary at this point in terms of their accuracy. Estimating the costs of such a complex industrial pivoting is difficult as it affects at a minimum the costs of developing and generating new products, the transformation of the pro duction lines and any potential losses from established products not manufactured during the given period 1 .…”
Section: Mass Production Of Testsmentioning
confidence: 99%
“…However, regional success stories involving, for instance, local test or tool production were reported from South Africa and Rwanda 95,96 . Although some initial cost estimates of the COVID19 disruption in the health care industry have been published [97][98][99] , they are likely to be too preliminary at this point in terms of their accuracy. Estimating the costs of such a complex industrial pivoting is difficult as it affects at a minimum the costs of developing and generating new products, the transformation of the pro duction lines and any potential losses from established products not manufactured during the given period 1 .…”
Section: Mass Production Of Testsmentioning
confidence: 99%
“…30 For those who do not accept the logic of utilitarianism, the expression ‘social utility’ certainly cannot be considered interchangeable with the expression ‘common good’. 32 …”
Section: Searching For the Best Possible Criterionmentioning
confidence: 99%
“…The economic case for stringent social distancing measures has been questioned due to their impact on the economy and livelihoods. 5 , 6 A cost-benefit analysis of government responses to Covid-19 requires an infectious disease model to project the counterfactual of what would have happened in the absence of government intervention. The first wave of Covid-19 in Europe was largely complete by July 2020; complete data on observed outcomes are therefore available for comparison with modelled outcomes, and it is thus possible to compare the costs and benefits of Government responses to this first wave.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Miles (2020) compared predictions of outcomes under no mitigation to observed outcomes up to June 2020, using an informal estimate of 5 QALYs lost per death. 6 They compared the reductions in actual GDP growth forecasts to costs and QALYs saved by government response. They found that continuing the lockdown was only cost-effective at a willingness-to-pay per QALY between £220 000 and £3.7 million.…”
Section: Introductionmentioning
confidence: 99%